Neuronal Cell Death and Mice (Mus Musculus) Behaviour after Induced by Bee Venom - Rian Oktiansyah; Berry Juliandi; Kanthi Arum Widayati; Vetnizah Juniantito (Tropical Life Sciences Research, 2018)
Neuronal cell death can occur in a tissue or organ, including the brain, which affects memory. The objectives of this study were to determine the dose of bee venom that causes neuronal death and analyse the alteration of mouse behaviour, focusing in particular on spatial memory. Fifteen male mice of Deutsche Denken Yoken (DDY) strain were divided into control and treatment groups. Bee venom was injected six times for two weeks intraperitoneally with 1.88 mg/kg, 3.76 mg/kg, 5.6 mg/kg, and 7.48 mg/kg doses of venom. Brain histology was studied using haematoxylin-eosin stained paraffin embedded 5 ?m coronal sections. A Y maze test was used to assay behaviour. Parameters observed were the number of dead neurons and the percentage of mice with altered behaviour. ANOVA showed that the effects of bee venom were significantly different in the case of the neuronal death parameter but were not significantly different in the case of the mice behaviour parameter. Duncan’s Multiple Range Test (DMRT) demonstrated that P4 (7.48 mg/kg) gave the highest effect of bee venom to promote neuronal death.